Numerical Study of Pillars Behavior in Continuous Miner Depillaring Panel: A Case Study - Chawla S.; Jaiswal A.; Shrivastva B.K. (My University, 2025)
The study aims to evaluate the pillar behavior during the depillaring operation by continuous miner (CM) technology. A panel with five headings developed as per the coal mine regulation of Indian coal mines [2] has been selected for the study. The depillaring operation has been carried out using CM technology after widening and heightening the original entries. An extensive field investigation has been carried out throughout the depillaring operation to access the mining conditions. Depillaring operation has been performed smoothly up to the middle of the panel (fourth row out of eight rows of four pillars each). Advanced blinking of the auto warning tell-tale (AWTT) has also been observed on some of the instruments during the splitting of pillar no. 18. The panel shows extremely difficult mining conditions at this stage. The case has been numerically simulated using three-dimensional numerical techniques. The simulation result has indicated the high stress and yield condition on the working and the barrier pillar (surrounding goaf from both sides) after the extraction of pillar no. 18. The analysis has also indicated the marginal stability of the 2nd barrier pillar (namely “pillar B”). The failure of the barrier pillar could be the responsible for global instability of the panel as observed in the field. Understanding the importance of the barrier pillars, panel design has been modified by incorporating an additional row of barrier pillars. The stability of the modified panel has been evaluated. Both working and barrier pillars have been observed stable in the modified panel. This could be an alternative layout considering safety at the working face. © 2022, Society for Mining, Metallurgy & Exploration Inc.